The role of phosphodiesterase activity on the temperature-dependent responses of calf cardiac vein - (:unkn) unknown (COMENIUS UNIV, 2013)
Objective: To evaluate the role of phosphodiesterase (PDE) activity in the cooling (to 28 degrees C) and warming (41 degrees C)-induced effects of carbachol on calf cardiac vein. Material and methods: Rings obtained from calf hearts were suspended in organ baths containing 25 ml of Krebs-Henseleit solution, maintained at 37 degrees C, continuously gassed with 95%O-2-5%CO2. At the end of the resting period the preparations were contracted with carbachol (10(-9)-3x10(-4)M), at 37 degrees C. The same protocol was repeated at 28 degrees C and 41 degrees C after the preparations were allowed to equilibrate at this temperature for 60 min. In order to analyze the role of PDE activity in the cooling-and warming-induced vascular response, carbachol (10(-9)-3x10(-4)M) was applied in the presence of cilostazol (10(-6) M), IBMX (10(-6) M) and rolipram (10(-6) M), respectively. Results: The sensitivity of carbachol was significantly lower during cooling, and higher during warming. Cooling to 28 and warming to 41 degrees C, after treatment with IBMX, cilostazol or rolipram, significantly decreased the sensitivity to carbachol (p<0.05). Conclusion: The results of the present study suggest that PDE activity plays an essential role in cooling-and warming-induced changes of calf cardiac vein treated with carbachol (Tab. 1, Fig. 2, Ref. 34). Text in PDF www.elis.sk.
Keywords: cardiac vein; carbachol; phosphodiesterase enzyme; cooling; warming; CYCLIC-NUCLEOTIDE PHOSPHODIESTERASE; CONTRACTILE AGENTS; CORONARY-ARTERY; INHIBITORS; PDE4; VASOCONSTRICTION; NORADRENALINE; EXPRESSION; REACTIVITY; CAMP